Solid Lipid Nanoparticles Co-loaded with Simazine and Atrazine: Preparation, Characterization, and Evaluation of Herbicidal Activity - Oliveira, Jhones Luiz de [UNESP]; Ramos Campos, Estefania Vangelie [UNESP]; Goncalves da Silva, Camila Morais; Pasquoto, Tatiane; Lima, Renata; Fraceto, Leonardo Fernandes [UNESP] (Amer Chemical Soc, 2015)
Solid lipid nanoparticles (SLN) containing the herbicides atrazine and simazine were prepared and characterized, and in vitro evaluation was made of the release kinetics, herbicidal activity, and cytotoxicity. The stability of the nanoparticles was investigated over a period of 120 days, via analyses of particle size, zeta potential, polydispersion, pH, and encapsulation efficiency. SLN showed good physicochemical stability and high encapsulation efficiencies. Release kinetics tests showed that use of SLN modified the release profiles of the herbicides in water. Herbicidal activity assays performed with pre- and postemergence treatment of the target species Raphanus raphanistrum showed the effectiveness of the formulations of nanoparticles containing herbicides. Assays with nontarget organisms (Zea mays) showed that the formulations did not affect plant growth. The results of cytotoxicity assays indicated that the presence of SLN acted to reduce the toxicity of the herbicides. The new nanoparticle formulations enable the use of smaller quantities of herbicide and therefore offer a more environmentally friendly method of controlling weeds in agriculture.
Keywords: environmental nanotechnology; herbicides; nanoparticles; herbicidal activity